The Lifestyle of Health and Sustainability Framework in Agricultural Community - Rizeki Dwi Fibriansari; Anggia Astuti; Leersia Yusi Ratnawati (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: The Lifestyle of Health and Sustainability (LOHAS) concept encourages life choices and adopting behaviors that prioritize both environmental sustainability and personal well-being. Lifestyle shifts and food consumption patterns are significant factors that often hinder the pursuit of a healthy and sustainable way of living. The purpose of this research is to explore the concept of LOHAS and its role in addressing the fundamental health needs of agricultural communities.Method: This study employs a descriptive-analytic method with a cross-sectional design. A sample of 138 fish cage farmers was selected. Primary data were collected through interviews using questionnaires and direct observations, focusing on aspects such as physical fitness, mental and emotional health, spiritual well-being, environmental awareness, and social responsibility. The data were analyzed descriptively.Result: The majority of fish cage farmers are males over the age of 50 years old. Aging farmers face physical and health challenges that can impact their productivity and long-term sustainability. Optimal physical health in agricultural communities can be supported through a balanced diet and regular exercise. Moreover, mental and emotional well-being can be enhanced through stress-relief activities, meditation, and fostering positive relationships. Adopting a holistic health approach enables communities to address physical, mental, emotional, and environmental aspects in alignment with the LOHAS framework.